2013
DOI: 10.2298/avb1303237k
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological characteristics of abomasal ulcers in high-yielding dairy cows

Abstract: The aim of this paper was to investigate the morphology, localization and typization of abomasal ulcers in high-yielding dairy cows, as a contribution to the existing knowledge on the subject. A total of ten high-yielding dairy cows which died during the period of early puerperium and two Holstein heifers which died in late pregnancy after transport to a new location were investigated in this study. Samples of altered abomasal tissue were taken at necropsy for further histopathology and mycology investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Rumen bacteria have played role resulting production of volatile fatty acids and lactic acid thereby decreasing / disturbing the rumen pH to non-physiological levels, reducing efficiency of rumen microflora. Acid indigestion which develops as the result of inadequate diet in the present study can also contribute to the development of ulcers, as reported by Kureljusic et al(2013).…”
Section: Resultssupporting
confidence: 80%
“…Rumen bacteria have played role resulting production of volatile fatty acids and lactic acid thereby decreasing / disturbing the rumen pH to non-physiological levels, reducing efficiency of rumen microflora. Acid indigestion which develops as the result of inadequate diet in the present study can also contribute to the development of ulcers, as reported by Kureljusic et al(2013).…”
Section: Resultssupporting
confidence: 80%
“…Proposed pathways through which stress could cause abomasal damage have a common starting point, whose involvement has been demonstrated only in rats. In rats, ulcers caused by stress only develop after a drop in body temperature (Weiner, 1996), which initiates 2 main pathways: (1) increased production of gastric acids, whose effects were described previously (see section titled Low Abomasal pH); and (2) a decrease in the rhythm of stomach contractions from 6 to 7 to only 0.5 to 2 times per minute, which leads to decreased mucosal blood flow and subsequent damage through local hypoxia, mechanical damage, and decreased function of the mucosa-protecting mucus and cytoprotective prostaglandins (Weiner, 1996;Marshall, 2009;Kureljušić et al, 2013).…”
Section: The Factor Of Stressmentioning
confidence: 90%
“…Abomasal damage involves lesions of the inner wall of the ruminant abomasum, which include minor perturbations or more severe damage causing bleeding or perforation of the wall and subsequent peritonitis. Abomasal damage is a problem in cattle of all ages and all production systems, with "white" veal calves (hereafter, veal calves) being most affected (e.g., Brscic et al, 2011;Kureljušić et al, 2013;Hund et al, 2016). Abomasal damage in the form of lesions can cause high mortality rates of, for example, between 0.53 and 0.11% in veal calves in Switzerland and Belgium (Bähler et al, 2012;Pardon et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Abomasal ulcers, local processes of autodigestion of the mucosa (Kureljušid et al, 2013), represent a significant economic problem and an animal welfare concern. They are an important cause of indigestion in dairy cows, feed-lot beef cattle and calves (Braun et al, 1991;Marshall, 2009).…”
mentioning
confidence: 99%
“…Nevertheless, they seem to be more prevalent in grazing dairy cows in the spring and early summer, and in those cows that have concomitant illnesses (Ceelen, 2010). Abomasal ulcers are the result of pathophysiological conditions, where the balance between the protective and destructive processes is disturbed (Kureljušid et al, 2013). In consequence, the resistance of abomasal mucosa is reduced, due to an increase in the secretion of corticosteroids, gastric acid and pepsin in combination with a decreased synthesis of prostaglandins (Braun et al, 1991).…”
mentioning
confidence: 99%